2018
DOI: 10.1017/s0025315418001108
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuation in food sources of herbivorous gastropods in a subtropical seagrass bed estimated by stable isotope analysis

Abstract: Various herbivorous invertebrates in seagrass beds are considered to be generalists in food use and their diets may temporally fluctuate according to the availability of food sources. We assessed whether food sources of herbivorous gastropods vary in a subtropical seagrass bed in Nagura Bay, Ishigaki Island, where coexisting seaweeds grow densely in spring but minimally in summer. Abundant gastropods and their possible food sources were collected in spring and summer of 2013 and 2015, and their stable carbon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…However, the nutrient content, cellulose shoot, and palatability of seagrasses are distinctly different from those of most macroalgae. Similar to our findings of the seagrass beds around Dongsha Island, stable isotope analysis also showed that macroalgae were generally the main food sources of herbivores in other tropical seagrass ecosystems [58][59][60]. For better resolution of production, consumption, and energy flows, we suggest distinguishing seagrasses and macroalgae as different compartments of primary producers when constructing trophic models of seagrass beds.…”
Section: Discussionsupporting
confidence: 86%
“…However, the nutrient content, cellulose shoot, and palatability of seagrasses are distinctly different from those of most macroalgae. Similar to our findings of the seagrass beds around Dongsha Island, stable isotope analysis also showed that macroalgae were generally the main food sources of herbivores in other tropical seagrass ecosystems [58][59][60]. For better resolution of production, consumption, and energy flows, we suggest distinguishing seagrasses and macroalgae as different compartments of primary producers when constructing trophic models of seagrass beds.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, substantial temporal variation in the stable isotopes of POM and macroalgae was also found in Zostera marina and Cymodocea nodosa seagrass meadows (Vizzini and Mazzola, 2003;Mittermayr et al, 2014), respectively. Such seasonal variations may be attributed to environmental factors and/or biotic physiological processes (Mittermayr et al, 2014;Jankowska et al, 2019;Nakamoto et al, 2019).…”
Section: Isotope Ratios Characteristics Of Food Sourcesmentioning
confidence: 99%
“…It is possible, because the absolute decomposition of seagrass dead leaves takes longer compared with macroalgae (Lavery et al, 2013;Liu et al, 2016b;Trevathan-Tackett et al, 2020), which might accumulate adequate food for the diet of detritivores. Meanwhile, seagrass meadows in tropical regions may accumulate more seagrass debris than those in temperate regions as a result of relatively mild seasonal changes (Nakamoto et al, 2019). Therefore, adequate seagrass detritus throughout the year in tropical seagrass meadows might keep the transfer pathway of carbon derived from seagrass stable along the detritus food chain (Figure 5).…”
Section: Flow Of Seagrass Carbon In Food Web and Its Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…They not only provide a nursery ground, habitat, shelter, and grazing areas for a large quantity of fish and invertebrates (Heck et al 2003, Unsworth et al 2019) but also provide rich organic carbon sources to support their food webs (Jinks et al 2019, Jänes et al 2020a, b, Jiang et al 2020). These organic carbon sources are usually very diverse, mainly including dead and living seagrass vegetation, epiphytes, macroalgae, particulate organic matter (POM, including phytoplankton), and microphytobenthos in the sediment (Smit et al 2005, 2006, Baeta et al 2009, Nakamoto et al 2019. The flow of organic carbon is mainly through grazing and detritus food chains (Patricio and Marques 2006).…”
Section: Introductionmentioning
confidence: 99%